Penggunaan Media Pembelajaran Wordwall untuk Meningkatkan Hasil Belajar IPAS Siswa Kelas V SD Inpres Tello Baru III Kecamatan Manggala Kota Makassar - Srirahayunur; Riang Tati, Andi Dewi; Utami, Unga (PT Ininnawa Paramacitra Edukasi, 2025)
This study has a formulation of the problem that was found and studied, namely how to utilize Wordwall learning media to improve the learning outcomes of fifth grade students of SD Inpres Tello Baru III, Manggala District, Makassar City. This study aims to describe the utilization of Wordwall learning media to improve the learning outcomes of fifth grade students of SD Inpres Tello Baru III, Manggala District, Makassar City. The type of research used is classroom action research (PTK) which includes 4 stages with a qualitative descriptive research approach. Based on the results of the study, it is known that the completion of the learning outcome test in cycle I has not reached classical completion because it is in the sufficient category. then in cycle II there was a significant increase in learning outcomes with student completion in the good category. Likewise with the teacher's teaching activities in cycle I with the sufficient category, then there was an increase in cycle II with the good category. In line with this, student learning activities also increased starting from cycle I with the sufficient category, then there was an increase in cycle II with the good category. The conclusion of the research results is that the use of Wordwall learning media can improve the science learning outcomes of grade V students of SD Inpres Tello Baru III, Manggala District, Makassar City.